ESTIMASI KEBUTUHAN MANGROVE DALAM MENDUKUNG KEGIATAN TAMBAK UDANG INTENSIF DI KECAMATAN BANYUPUTIH KABUPATEN SITUBONDO - Abdul Muqsith; Nurdin Harahab; Mohammad Mahmudi; Muhammad Fadjar (Samakia : Jurnal Ilmu Perikanan, 2018)
Intensive shrimp farms need mangroves to increase the carrying capacity of their waters. Every 1 Ha of intensive shrimp pond requires 7.2 Ha mangrove to absorb nitrogen (N) and 21,7 Ha to absorb phosphor (P) from waste water disposal. This study was conducted to estimate the extent of lmangrove required to absorb nitrogen (N) and phosphorus (P) wastes removed from intensive shrimp farming in Banyuputih Subdistrict of Situbondo Regency. From the field survey results obtained data on the area of ​​productive intensive ponds in the District Banyuputih is 39 Ha. The result of data analysis indicate that 280,3 Ha mangrove is needed to support the absorption of nitrogen (N) and 846,3 Ha mangrove to absorb phosphorus (P) of effectiveness pond waste pond in the study area. The mangrove in this subdistrict of Banyuputih (540,18 Ha) still support in the absorption of nitrogen waste (N), but for the absorption of phosphorus posfor (P) ponds still needed reforestation of at least 304,12 Ha from the existing mangrove area. If the local government intends to develop intensive shrimp ponds in accordance with the carrying capacity or maximum capacity of coastal waters of Banyuputih in decomposing 58 ha of tambak organic ponds, the current mangrove condition (540.18 Ha) still supports the absorption of nitrogen (N) from ponds intensively covering an area of ​​58 Ha, but to absorb the posfor (P) lagoon is still needed addition (reforestation) of 718.42 Ha.